2016
DOI: 10.4067/s0717-97072016000300014
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis of Alkaloids From the Chilean Endemic Tree Cryptocarya Alba

Abstract: A phytochemical study of the roots and aerial parts of Cryptocarya alba (Mol.) Looser (Lauraceae), an endemic Chilean tree and the southernmost Cryptocarya species, led for the first time to the isolation and unambiguous characterization of four known alkaloids by NMR techniques: boldine, laurolitsine, laurotetanine and norglaucine, in addition to the previously identified reticuline, and the identification via UHPLC-MS of seven more alkaloids, coclaurine, N-methylcoclaurine, norreticuline, isocorydine, N-meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 13 publications
0
13
1
Order By: Relevance
“…In agreement with our results, Timmermann et al [26], also reported flavonoids (isorhamnetin, kaempferol, quercetin, and their glycosides) and chlorogenic acid present in leaves extract of peumo. In contrast to the previous report of Castro-Saavedra et al [27], no alkaloid was detected by U-HPLC/MS. Both fruit extracts showed the presence of quercetins and their derivatives.…”
Section: Discussioncontrasting
confidence: 99%
“…In agreement with our results, Timmermann et al [26], also reported flavonoids (isorhamnetin, kaempferol, quercetin, and their glycosides) and chlorogenic acid present in leaves extract of peumo. In contrast to the previous report of Castro-Saavedra et al [27], no alkaloid was detected by U-HPLC/MS. Both fruit extracts showed the presence of quercetins and their derivatives.…”
Section: Discussioncontrasting
confidence: 99%
“…The alkaloid composition of the branches (wood and bark) is largely consistent with results obtained previously. 10 In 67% of the individuals, laurolitsine was the most abundant wood alkaloid, while laurotetanine and reticuline predominated in the bark. In 88% of the trees, reticuline was the major bark alkaloid, but exceptions were found in the southern population, with laurotetanine predominating in the bark of 6 individuals, and reticuline in the wood of another 7, while only 2 individuals had both high bark laurotetanine and wood reticuline.…”
mentioning
confidence: 94%
“…31 In our earlier work on C. alba, the best results for leaves were obtained from young saplings (<3 years old). 10 Therefore, a detailed analysis of farmed individuals was deemed important. The amount of sunlight can influence the yield of some alkaloids so we compared subpopulations with different degrees of shading.…”
mentioning
confidence: 99%
See 2 more Smart Citations